2011
DOI: 10.1210/en.2010-1485
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Ghrelin Deficiency Compromises Reproduction in Female Progeny through Altered Uterine Developmental Programming

Abstract: Ghrelin has a well-known role in the regulation of appetite, satiety, energy metabolism, and reproduction; however ghrelin has not been implicated in reproductive tract development. We examined the effect of ghrelin deficiency on the developmental programming of female fertility. We observed that female wild-type mice born of ghrelin heterozygote dams (i.e. exposed in utero to ghrelin deficiency) had diminished fertility and produced smaller litters. We demonstrate that exposure to in utero ghrelin deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
2
19
0
4
Order By: Relevance
“…It is interesting that a similar tendency was observed in adult females exposed to intragestational GHRL imbalances. A remarkable study by Martin et al (2011) demonstrated a significantly lower implantation index in female mice exposed to intragestational GHRL deficiency (similar to our Ant treatment), explained by impaired endometrial function. As in our study, they did not find any alterations in ovarian follicles or corpora lutea (Martin et al 2011).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It is interesting that a similar tendency was observed in adult females exposed to intragestational GHRL imbalances. A remarkable study by Martin et al (2011) demonstrated a significantly lower implantation index in female mice exposed to intragestational GHRL deficiency (similar to our Ant treatment), explained by impaired endometrial function. As in our study, they did not find any alterations in ovarian follicles or corpora lutea (Martin et al 2011).…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, the information obtained from these studies about the physiological role of GHRL during pregnancy is limited. Moreover, to our knowledge, there is only one study of the effects of maternal GHRL deficiency (comparing homozygote with heterozygote dams) on reproductive foetal programming of female offspring (Martin et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study using ghrelin heterozygous mice reported that a systemic low level of maternal ghrelin appeared to have an adverse effect on the uterine programming of their wild-type female offspring, causing subnormal fertility rates through reduced implantation, despite normal ovarian function and embryo production [19]. These authors suggested that their findings could have serious implications for the fertility of women born to obese mothers who would have had blunted ghrelin levels due to their obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin-immunoreactive neurons are present in few regions of the brain like the arcuate and the ventromedial nucleus of the hypothalamus, cerebellum and brainstem [12,[18][19][20]. Ghrelin is also present in placenta along GH, GHRH, somatostatin and insulin-like growth factor 1 (IGF1) which shows that it is also involved in fetal growth [21].…”
Section: Observationmentioning
confidence: 99%